‘Inter-ideologicality’ in intercultural communication education: co-constructing criticality around the concept of culture in international online student mobility - Peng, Jun; Dervin, Fred (Frontiers in Communication, 2024)
The world has been experiencing huge upheavals since the COVID-19 crises. Conflicts caused by opposing ideologies, economic-political agendas and realities are rampant within or across borders. Such unsteady circumstances contribute to shifting how Transnational Education (TNE) occurs worldwide, as well as the scientific, epistemic and educational discourses that go with it. Anchored within critical interculturality, this paper explores the concept of ‘inter-ideologicality’. The study looks at short-term online international student mobility to demonstrate how students from China and Finland navigate and negotiate ideologies around the concept of culture in intercultural research and education. The study also employs Wang Chong’s perspectives on criticality to identify emerging ideologies in the co-construction of criticality in students’ online cooperation. Findings reveal that (1) two ideological orientations, nation-oriented and society-oriented, developed during discussions about culture; (2) Finnish students used a specific form of reasoning to contradict Chinese students’ thoughts about Finland by means of criticality towards the nation-oriented ideology; (3) Chinese and Finnish students employed questioning and challenging to help each other be aware of something left unsaid about the status of women in their societies within the society-oriented ideology. The study represents an important meta-approach to intercultural communication education within internationalization of Higher Education, aimed at supporting mobile students to reflect critically on the scientific and educational notion of interculturality rather than providing them with ready-made recipes as to how to communicate and behave interculturally.